2019
DOI: 10.31557/apjcp.2019.20.6.1649
|View full text |Cite
|
Sign up to set email alerts
|

Relative Expression of OCT4, SOX2 and NANOG in Oral Squamous Cell Carcinoma Versus Adjacent Non- Tumor Tissue

Abstract: Objective: Oral squamous cell carcinoma (OSCC) accounts for over 90% of oral neoplasms. Finding molecular markers for predicting prognosis is a high priority. The core transcription factors, OCT4, SOX2, and NANOG that regulate embryonic stem cell pluripotency have been implicated in progression of various malignancies. The predictive value of these markers and their role in the development of OSCC is still controversial. In this study, we therefore evaluated their expression in OSCCs and adjacent non-tumor tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…Low expression level of Nanog was reported with tumor adjacent specimens and early stages (PT/N0, stages I and II) of OSCC 14,15 . Contrary to these reports, our results support Nanog as a higher stage OSCC biomarker 16,18‐20 . Nanog is documented to increase with OSCC progression (AN < WDSCC < MDSCC < PDSCC), 25 lymph node metastasis, 16 advanced cancer stage/worse prognosis, 39 preoperative adjuvant therapy resistance, 25 EMT and stemness 40 .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Low expression level of Nanog was reported with tumor adjacent specimens and early stages (PT/N0, stages I and II) of OSCC 14,15 . Contrary to these reports, our results support Nanog as a higher stage OSCC biomarker 16,18‐20 . Nanog is documented to increase with OSCC progression (AN < WDSCC < MDSCC < PDSCC), 25 lymph node metastasis, 16 advanced cancer stage/worse prognosis, 39 preoperative adjuvant therapy resistance, 25 EMT and stemness 40 .…”
Section: Discussioncontrasting
confidence: 95%
“…Some studies suggest that Nanog is an early predictor of oral cancer risk 14 based on its expression in the tumor adjacent uninvolved tissue 15 . Another study failed to find any statistically significant differences for the expression of Nanog in OSCC 16 . Hwang et al in 2014 found no association of Nanog expression with clinical stage of OSCC 17 .…”
Section: Introductionmentioning
confidence: 99%
“…85,86 Additionally, Sox2 is an independent prognostic factor for OSCC, since decreased Sox2 expression is correlated with oral cavity carcinogenesis and development of OSCC. 87,88 All these discoveries indicate that the above embryonic stem cells-related transcription factors may be involved, at least in part, in OSCC EMT and tumor metastasis ( Table 1).…”
Section: Zeb Familymentioning
confidence: 99%
“…However, Li et al (59) demonstrate that SOX2 is a downstream target of the Hippo effector TAZ in HNcSCC, which is capable of reprogramming differentiated cancer cells into CSCs, and that SOX2 and TAZ upregulation are both associated with poorer overall survival in HNcSCC. Given the presence of SOX2 in mHNcSCC (60) and its association with local recurrence and metastasis, we speculate the TAZ-SOX2 axis as an important determinant of CSC stemness in this tumor. The low expression of SOX2 within mHNcSCC-derived primary cell lines and the lower proportions of SOX2 positive cells in mHNcSCC tissue samples on IHC staining and ISH staining compared to the other four iPSC markers may reflect the aggressiveness of this cancer, as decreased SOX2 expression has been associated with carcinogenesis and the development of OCSCC (60).…”
Section: Discussionmentioning
confidence: 87%
“…Given the presence of SOX2 in mHNcSCC (60) and its association with local recurrence and metastasis, we speculate the TAZ-SOX2 axis as an important determinant of CSC stemness in this tumor. The low expression of SOX2 within mHNcSCC-derived primary cell lines and the lower proportions of SOX2 positive cells in mHNcSCC tissue samples on IHC staining and ISH staining compared to the other four iPSC markers may reflect the aggressiveness of this cancer, as decreased SOX2 expression has been associated with carcinogenesis and the development of OCSCC (60).…”
Section: Discussionmentioning
confidence: 87%